AN INVESTIGATION INTO TOPIC-COMMENT SENTENCES IN ENGLISH AND VIETNAMESE IN THE PERSPECTIVE OF NEGATIVE TRANSFER - Assoc. Prof. Dr. PHAN VĂN HÒA (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is confined to the investigation of TCSs in the perspective of Vietnamese-English negative transfer. It does not attempt to prove any underlying grammatical structure of Vietnamese and English sentences revealed through students’ negative transfers. Instead, the thesis focuses on the basic structures of TCSs in the two languages. Moreover, within the scope of a thesis, we cannot cover all the negative transfer but tend to rely on some as a research tool for examining whether the STCSs of Vietnamese is one of the possible hindrances causing difficulty for students in their translation tasks.